Ásatrú: An Enchanting Hybrid of Past and Present - Dijk, Lotte, 1992- (2017)
The relatively recent attempt to reconstruct Old Norse religion in Iceland, resulting in the establishment of an Ásatrú community, could be motivated by the wish of preserving cultural tradition, but might possibly be an indicator of another kind of wish as well, that is, for the re-enchantment of the disenchanted modern world through the return to a simple and “magical” past. To verify this, Old Norse religion and Icelandic Ásatrú have been analysed and compared using Robert N. Bellah’s theory of religious evolution. This qualitative study found that these religious systems share a specific primitive/archaic religious configuration. The correspondence of this configuration with one found in previous research implies the existence of an ideal religious system concerning the need for re-enchantment. A system based on pre-Christian pagan religion in conjunction with the mind-set of people in modern society. This combination of the old and the new creates an interesting dichotomy which, when analysed in relation to the notions of disenchantment, re-enchantment, neomedievalism and neopaganism, appears to be a success formula with regard to re-enchanting modernity’s rational reality. This religious configuration provides an alternative enchanting worldview, which is a critique of modernity, yet at the same time it is conditioned by it; a “religionism” of which Ásatrú is an example as well.